The scale of myths of romantic love: Evidence of validity and reliability of a brief scale in Peru - Ventura-León, José (2024)
The study aimed to provide validity evidence and reliability of the Scale of Myths of Romantic Love (SMRL) in Peru among young and adult individuals. Focusing on how romantic love myths affect relationship satisfaction and their ties to interpersonal violence, sexism, and gender inequality, the methodology involved 308 participants, mainly females (75%), using the SMRL and Relationship Assessment Scale. Bayesian Confirmatory Factor Analysis (BCFA) assessed the scale's structure and reliability, complemented by descriptive statistics and correlation analyses to examine the myths' impact on intimate relationships. Results showed the SMRL's two-dimensional structure, confirming its robust psychometric properties and satisfactory internal consistency. Descriptive findings revealed a skeptical view of traditional romantic myths among participants, indicating the scale's good reliability and successful adaptation to the Peruvian context. This validation highlights how debunking romantic love myths can improve relationship dynamics and satisfaction and addresses their wider societal effects.